Evaluación de la degradación de diésel mediante Bacillus sp. Antárticos - Palacios García, Dayana Mercedes (2023)
The objective of this research was to evaluate the biodegradation capacity of petroleum hydrocarbons (diesel) through the application of Bacillus sp isolated from Antarctica. The study was carried out under the completely randomized block design experimental model (DBCA) unifactorial and three blocks made up of five treatments (strains) with three repetitions in each period (24, 48 and 72 hours) with a total of 45 units experimental. The isolated strains were adapted to a medium of mineral salts enriched with diesel under controlled conditions. The halo of degradation carried out by each one of the strains evaluated, supplying diesel as the only carbon source. Statistical analysis was carried out using an analysis of variance (ANOVA) and Tukey's test to determine significant differences. The most representative biodegradation percentages were 52% (GA-52); 43% (T-21) and 39% (T-13). In conclusion, the GA-52 treatment has a higher capacity to degrade diesel compared to the other strains studied under the controlled conditions in the present experiment.